PELATIHAN BAHASA INGGRIS UNTUK PEREMPUAN WIRAUSAHA DI KAMPUNG HERITAGE KAJOETANGAN, KOTA MALANG - Novitasari Novitasari; Tiara Estu Amanda; Hiqma Nur Agustina; Maya Rizki Fauzia; Nugrahaningtyas Fatma Anyassari; Noverita Wahyuningsih (P3M Politeknik Negeri Malang, 2023)
City tourism is one of the attractions that can be visited by local and foreign tourists. City tourismhas various types of attractions, one of which is a tourist village. Tourism villages can improve thelocal community's economy and have the competitiveness to become the leading tourism in a city.Kajoetangan Heritage Village, which is located in Malang City, has tourism potential because it hasthe characteristics of a row of houses with Dutch colonial architecture that are still original andwell preserved. In addition, in this tourist village there are also entrepreneurs who are dominatedby women. This business has the potential to boost the economy by selling superior products andservices to tourists. This training aims to improve the English language skills of womenentrepreneurs in offering and selling their products to foreign tourists. As a result, participants areable to demonstrate skills in conducting conversations in English to sell and offer products andservices.